Multi-criteria computational screening of [BMIM][DCA]@MOF composites for CO2 capture - Mengjia Sheng; Xiang Zhang; Hongye Cheng; Zhen Song; Zhiwen Qi (Green Chemical Engineering)
Ionic liquid (IL) can be inserted into metal organic framework (MOF) to form IL@MOF composite with enhanced properties. In this work, hypothetical IL@MOFs were computationally constructed and screened by integrating molecular simulation and convolutional neural network (CNN) for CO2 capture. First, the IL [BMIM][DCA] with a large CO2 solubility was inserted into 1631 pre-selected Computational-Ready Experimental (CoRE) MOFs to create hypothetical IL@MOFs. Then, given the temperature and pressure of adsorption and desorption, the CO2/N2 selectivity and CO2 working capacity of 700 representative IL@MOFs were assessed via molecular simulations. Based on the results, two CNN models were trained and used to predict the performance of other IL@MOFs, which reduces the computational costs effectively. By combining the simulation results and CNN model predictions, 22 IL@MOFs with top-ranked performance were identified. Three distinct ones IL@HABDAS, IL@GUBKUL, and IL@MARJAQ were chosen for explicit analysis. It was found that a desired balance between CO2/N2 selectivity and CO2 working capacity can be obtained by inserting the optimal number of IL molecules. This helps guide a novel design of IL@MOF composites with advanced performance on carbon capture.